2014
DOI: 10.1016/b978-0-12-800179-0.00001-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides, Trophic Factors, and Other Substances Providing Morphofunctional and Metabolic Protection in Experimental Models of Diabetic Retinopathy

Abstract: Any queries or remarks that have arisen during the processing of your manuscript are listed below and are highlighted by flags in the proof. (AU indicates author queries; ED indicates editor queries; and TS/TY indicates typesetter queries.) Please check your proof carefully and answer all AU queries. Mark all corrections and query answers at the appropriate place in the proof (e.g., by using on-screen annotation in the PDF file http:// www.elsevier.com/book-authors/science-and-technology-book-publishing/overvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 391 publications
(477 reference statements)
2
23
0
Order By: Relevance
“…The relationship between PACAP and several molecules measured by the angiogenesis array is still unclear, but it can be concluded that PACAP reduced the secretion of several proangiogenic factors in retinal pigment epithelial cells. In our previous studies, on the possible effects of PACAP in diabetic retinopathy, it was also proven that PACAP treatment can ameliorate the vascular changes . Thus, PACAP might be a potent drug against retinopathies with angiogenic processes in the background.…”
Section: Discussionmentioning
confidence: 91%
“…The relationship between PACAP and several molecules measured by the angiogenesis array is still unclear, but it can be concluded that PACAP reduced the secretion of several proangiogenic factors in retinal pigment epithelial cells. In our previous studies, on the possible effects of PACAP in diabetic retinopathy, it was also proven that PACAP treatment can ameliorate the vascular changes . Thus, PACAP might be a potent drug against retinopathies with angiogenic processes in the background.…”
Section: Discussionmentioning
confidence: 91%
“…Zucker Diabetic Fatty rats have always been used in studies of type 2 diabetes related to obesity [5]. Their age range of diabetes onset is between ten weeks and twenty weeks [5].…”
Section: Zucker Diabetic Fatty Ratsmentioning
confidence: 99%
“…Zucker Diabetic Fatty rats have always been used in studies of type 2 diabetes related to obesity [5]. Their age range of diabetes onset is between ten weeks and twenty weeks [5]. This strain reproduces effectively and therefore is a common model in the disease pathophysiology, therapeutic interventions, and complications study of type 2 diabetes onset of young and middle-aged adults, giving examples like its effects on cardiac metabolism and function [2,6].…”
Section: Zucker Diabetic Fatty Ratsmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is a complication of diabetes that represents one of the major causes of vision loss in humans. The endogenous neuropeptide somatostatin has been widely studied for its powerful neuroprotective properties that may be exploited for DR treatment, and these studies have been extensively reviewed (Gabriel, 2013;Hernandez et al, 2014;Szabadfi et al, 2014;Simo-Servat et al, 2018;Cervia et al, 2019). In particular, the treatment with the somatostatin analog octreotide (OCT) has been found to inhibit apoptotic cell death and avoid vascular endothelial growth factor (VEGF) overexpression in retinal explants exposed to typical diabetic stressors such as hyperglycemia, oxidative stress (OS) or advanced glycation end-products (Amato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%